Meaning Term 'Qasam' in Tafsir al-Azhar Book’s: Analytical Study of Hamka's Interpretation in Surah al-Fajr 1-4 - Fajriyaturrohmah,; Daib Insan Labib, Muhammad Alfreda (Jurnal Usuluddin, 2025)
This article discusses meaning term qasam in Tafsir al-Azhar of surah al-Fajr verses 1-4. The discussion in this study includes information about Surah al-Fajr, interpretation qasam on surah al-Fajr in Tafsir al-Azhar by Hamka's, other examples of Hamka's interpretations in al-Qur’an, and the method and patterns of Hamka's interpretations. The method used in this research is qualitative with data collection methods through literature review. The data processing method is descriptive-analysis. This study concludes that, 1) Hamka interprets qasam in Surah al-Fajr as a form of emphasis from Allah SWT to His servants to maximize the time they have available; 2) Hamka tends to provide a broad perspective in interpreting. At least this can be proven by the interpretation of Tafsir al-Azhar non-mazhabi and tahlili.